Chondroprotectors in complex treatment of non-specific back pain: effectiveness evaluation - Elena B. Kuznetsova; Nikita S. Kuznetsov (ZAO "Consilium Medicum", 2023)
Background. Degenerative and dystrophic spinal diseases and associated pain syndrome remain a leading problem for practical health. The symptom-modifying and structurally modifying effects of chondrobrotectors suggest that they may be effective in treating patients with lower back pain (LBP). Aim. Study of the efficacy of Ambene® Bio in complex therapy of patients with acute LBP associated with degenerative dystrophic spinal diseases. Materials and methods. The article analyzes the results of examination and treatment of 50 patients with dorsopatia and non-specific LBP, who received treatment in hospital in the neurological department of Saratov City Clinical Hospital №9 or outpatient on the basis of the clinic "Artromedcenter" Saratov. Patients are randomly sampled into two groups of 25 people: those who received (core group) and those who did not receive (comparison group) Ambene® Bio therapy. The groups were comparable by sex, age, and clinical manifestations of dorsopathy. Methods of non-parametric analysis have been applied to statistical processing of the study results. The analysis included computing the median (Me) and quartile scale (Q25-Q75 - 25th and 75th percentiles). Results. All patients participating in the study noted improvement and reduction of pain syndrome during the treatment. The results of a survey using 100-point VAS indicate that on the 20th day of therapy (visit 2) the lower back pain syndrome significantly decreased from 66.1±8.54 to 23.32±6.76 (p0.05). In the comparison group the VAS dynamics pain was positive, but not so pronounced: before treatment - 70.11±11.43, on the 20th day of therapy - 46.15±9.38. The sum of test points on the Watkins scale in the core group did not exceed 15 points during the study, while in the HS the total scale was close to the value of 24 points. Conslusion. The use of Ambene® Bio promotes a faster onset of the analgesic effect - on the 7th day of therapy, pain was practically relieved in 56% of patients in the core group. This made it possible to reduce the dose and shorten the duration of the NSAID course.